Determinants Factors Related to Patient Satisfaction with Laboratory Services at Permata Hati General Hospital - Wangi, Ni Putu Ayu Cendana; Prihatiningsih, Diah; Nopita Wati, Ni Made; Cahyani, Anak Agung Ayu Eka; Yanti, Ni Luh Gede Puspita (Future Science, 2023)
Introduction: The quality of healthcare services is a crucial factor in the success of a hospital. Healthcare services are considered high-quality when they generate satisfaction for the patients served. This research aims to identify factors related to patient satisfaction with laboratory services. Methods: The research used a quantitative approach with a correlational research design and a cross-sectional approach. The sampling technique used in this study is purposive sampling. The sample size used in this research is 98 patients. The instrument used in this study is a patient satisfaction questionnaire consisting of 25 items. The questionnaire has been validated and has good reliability, with validity test values ranging from 0.477 to 0.980 and a reliability value of 0.913. Data processing in this research uses Chi-square and Rank Spearman tests. Results: The results of the study indicate that there is no relationship between age (p=0.100), gender (p=0.133), education (p=0.594), marital status (p=0.151), and occupation (p=0.155) with patient satisfaction. Conclusion: It can be concluded that age, gender, education, marital status, and occupation do not have a significant relationship with patient satisfaction with the services provided.